2005
DOI: 10.1152/ajpcell.00416.2004
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine production of prostaglandin F enhances phenotypic transformation of normal rat kidney fibroblasts

Abstract: We have used normal rat kidney (NRK) fibroblasts as an in vitro model system to study cell transformation. These cells obtain a transformed phenotype upon stimulation with growth-modulating factors such as retinoic acid (RA) or transforming growth factor-β (TGF-β). Patch-clamp experiments showed that transformation is paralleled by a profound membrane depolarization from around −70 to −20 mV. This depolarization is caused by a compound in the medium conditioned by transformed NRK cells, which enhances intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Washout of the medium conditioned by the transformed cells by perfusion with fresh serum-free medium causes the cells to slowly repolarize, and, preceded by a short period of fast small-amplitude spiking of their membrane potential ("fast oscillating state"), to regain spontaneous repetitive action potential firing activity ("AP-firing state") similar to that of the contact inhibited cells. These phenomena have been described in detail (23) and are very similar to the behavior of other cell types with calcium oscillations and action potential firing, such as interstitial cells of Cajal (24) and hepatocytes (25).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Washout of the medium conditioned by the transformed cells by perfusion with fresh serum-free medium causes the cells to slowly repolarize, and, preceded by a short period of fast small-amplitude spiking of their membrane potential ("fast oscillating state"), to regain spontaneous repetitive action potential firing activity ("AP-firing state") similar to that of the contact inhibited cells. These phenomena have been described in detail (23) and are very similar to the behavior of other cell types with calcium oscillations and action potential firing, such as interstitial cells of Cajal (24) and hepatocytes (25).…”
mentioning
confidence: 52%
“…4A and B obtained by stability analysis of the single-cell model provide an explanation for the various growth-state dependent changes in the electrophysiological behavior of normal rat kidney (NRK) fibroblasts in cell culture (23). The stability analysis of the single-cell model (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…COX-2-derived products such as prostaglandins are also known to affect cell growth of many renal cell types [19, 20] and their increased production in renal disease [21,22,23] may be of particular importance. Craven et al [24] demonstrated that PGH 2 /thromboxane A 2 -induced hypertrophy of rat vascular smooth muscle cells is mediated via protein kinase C-dependent increases in TGF-β, and Logan et al [25] demonstrated that the compensatory growth that occurs after uninephrectomy could be blocked by indomethacin, a non-selective inhibitor of both COX-1 and COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the cortical collecting duct, FP couples with a pertussistoxin-sensitive pathway to regulate water transport, rather than the usual G q -mediated responses. Moreover, in rat kidney fibroblasts, PGF 2α acting on FP causes cell transformation by increasing intracellular Ca 2+ and activating Ca 2+ -dependent Cl − channels [172]; future studies should determine whether the PGF 2α /FP system contributes to cell transformation in kidney diseases. Considering that a substantial amount of PGF 2α is produced in the kidney, the next decade will surely reveal a greater diversity of renal processes associated with activation of the PGF 2α /FP system.…”
Section: The Renal Pgf 2α /Fp Systemmentioning
confidence: 99%